Obesity among schooling adolescents in a school in Kuala Lumpur, 1994 - Othman Warijo,; Mohd Nasir Hashim, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Obesity is a current nutritional problem in developing countries, including Malaysia. A cross-sectional study was done in early 1994, at Sekolah Menengah Raja A1i, Kuala Lumpur, to determine the prevalence rate of obesity among schooling adolescents, and studying factors affect it. Methodology 300 samples was chosen randomly from all form I- V students, after stratified according to their form dan ethnicity .Personal, as well as, family, eating habit and information about physical activity, and respondents' nutritional knowledge and perception obtained using a self-administered questionaire. Weight, height, blood pressure and food frequency were then taken in a separate session. Body weight status was determined by Body Mass index (BMI) calculation. Nutrition intake was estimated using a computer package. Result Prevalence rate of obesity (BMI>25 00 kg/m2) was found to be 10.2 percent (2.2% was Grade II obese). Obesity was more prevalent with increasing age, but no difference by sex, ethnicity and religion. Obese adolescents was found to come from higher percapita income family (T=2.54; p<0.05) and have working mother (X2=4.54; p<0.05). Their nutritional knowledge were also superior from their counterparts (T=2.96; p<0.01). Percapita family income of Grade II obese adolescents were lower than Grade I obese adolescents', but was statistically not significant. There were trends that the obese adolescents were given more pocket-money, nibbling while studying, and have more sleep but less exercise, which were also statistically insignificant. Two out of :five Grade II obese adolescents were found to have mild hypertension. Blood pressure was significantly inceasing with the increament of BMI. Conclusion Obesity is occuring among adolescent in Kuala Lumpur, and need our attention as some of them have already develop hypertension.